Enhancing UTAR freshman mental health screening: integrating power automate to improve counselling support - Chua, Wen Xin (2025)
Depression may be the second most common global disease burden after HIV/AIDS in the year 2030. Approximately one million people in Malaysia aged 16 years and above suffer from depression. In alignment with ongoing efforts to promote mental health support, UTAR counsellors conducted mental health screening tests for freshmen using the Warwick-Edinburgh Mental Well-being Scale (WEMWBS) during orientation week. The WEMWBS test is designed to measure the mental well-being of individuals. However, the current screening process lacks immediate feedback or actionable suggestions for UTAR students. Additionally, there is uncertainty regarding the construct validity of the WEMWBS questionnaire in capturing the underlying psychological structure. Therefore, this research proposes an automated support system using Microsoft Power Automate to enhance UTAR freshman mental health screening procedures. The workflow may reduce the student's waiting period for support and the counsellors' workload by streamlining the management of student responses. Moreover, a series of multivariate analyses was conducted to gain deeper insight into the underlying structure of the well-being data. Particularly, Principal Component Analysis (PCA), Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), and Structural Equation Modelling (SEM) were applied to identify and validate the core dimensions of student mental well-being. A series of reliability analyses and convergent and discriminant validity were tested throughout the analysis. In conclusion, this research successfully achieved all the objectives by developing a working automation system and identifying key factors to student mental well-being. The EFA identified three underlying factors, namely Positive Emotion, Personal Growth, and Social Exploration. Among the three identified factors, Positive Emotion was the most influential. Promoting emotional positivity may most effectively enhance student well-being, offering a practical approach to improving university mental health support.